Modeling the influence of changing storm patterns on the ability of a salt marsh to keep pace with sea level rise. Issue 1 (27th January 2013) - Schuerch, M.; Vafeidis, A.; Slawig, T.; Temmerman, S.
Abstract: [1] Previous predictions on the ability of coastal salt marshes to adapt to future sea level rise (SLR) neglect the influence of changing storm activity that is expected in many regions of the world due to climate change. We present a new modeling approach to quantify this influence on the ability of salt marshes to survive projected SLR, namely, we investigate the separate influence of storm frequency and storm intensity. The model is applied to a salt marsh on the German island of Sylt and is run for a simulation period from 2010 to 2100 for a total of 13 storm scenarios and 48 SLR scenarios. The critical SLR rate for marsh survival, being the maximum rate at which the salt marsh survives until 2100, lies between 19 and 22 mm yr ‐1 . Model results indicate that an increase in storminess can increase the ability of the salt marsh to accrete with sea level rise by up to 3 mm yr ‐1, if the increase in storminess is triggered by an increase in the number of storm events (storm frequency). Meanwhile, increasing storminess, triggered by an increase in the mean storm strength (storm intensity), is shown to increase the critical SLR rate for which the marsh survives until 2100 by up to 1 mm yr ‐1 only. On the basis of our results, we suggest that the relative importance of storm intensity and storm frequency for marsh survival strongly depends on the availability of erodible fine‐grained material in the tidal area adjacent to the salt marsh. Key Points: High storminess increases the ability of salt marshes to adapt to sea level rise Increased storm frequency enhances marsh accretion stronger than storm intensity Availability of erodible sediment controls the storm influence on marsh survival